Green Synthesis, Characterization, and Evaluation of the Antimicrobial Activity of Camellia sinensis Silver Nanoparticles - Toga Khalid Mohamed; Marivt Osman Widdatallah; Maida Musa Ali; Afraa Mubarak Alhaj; DhiaEldin AbdElmagied Elhag (Journal of Nanotechnology)
An extremely worrying and alarming increase in the level of multiple drug resistance is reported in Sudan, in which bacterial strains are becoming resistant to many commonly available antibiotics. Eventually, it is becoming extremely difficult to treat debilitating infections. In search of promising solutions to this arising crisis, Camellia sinensis silver nanoparticles were synthesized using the green synthesis method. The synthesis of the Camellia sinensis silver nanoparticles is confirmed using analytical methods as ultraviolet-visible spectroscopy, X-ray diffractometer, and scanning electron microscopy. Using the ultraviolet-visible spectroscopy, an absorption band of 412 nm was observed. Furthermore, scanning electron microscopy revealed the presence of silver nanoparticles which fell within the range of 1–100 nm, and X-ray diffractometer analysis showed three intense peaks with a maximum intense peak at 24.3 theta. Nanoparticles distribution between 12 nm and 64 nm was observed with an average diameter of 18.115 nm. It also revealed orthorhombic-shaped nanoparticles. The synthesized nanoparticles showed antimicrobial activity against Staphylococcus aureus with a zone of inhibition of 7 mm, but none was detected against Escherichia coli. The obtained physicochemical properties were correlated with the antibacterial activity of the silver nanoparticles.